VALIDITAS KRITERIA SUBTES EAS 4 KETELITIAN DAN KECEPATAN VISUAL - Siwi Widiana, Herlina (Universitas Ahmad Dahlan, 2009)
The purpose of this research was to examine the criterion validity of EAS 4 visual speed and accuracy test. Score of EAS 4 visual speed and accuracy test was correlated with score of clerical speed and accuracy test from differential aptitude test (DAT) battery. The subjects of this research were 87 students of the Faculty of Psychology Ahmad Dahlan University.The data were obtained through EAS 4 visual speed and accuracy test and clerical speed and accuracy test (D4). Quantitative analysis was done by SPSS version 15 software. Product moment´s correlation analysis was used to test the relationship between score of EAS 4 visual speed and accuracy test and score of clerical speed and accuracy test (D4). The result of this research shows that there was a significant correlation (r=0,591; p=0,000) between score of EAS 4 visual speed and accuracy test and score of clerical speed and accuracy test (D4). It means that EAS 4 visual speed and accuracy test had good criterion validity to measure perceptual ability.